2014
DOI: 10.1371/journal.pone.0087813
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Renin Angiotensin Axis May Be Associated with Reduced Risk of Developing Venous Thromboembolism in Patients with Atherosclerotic Disease

Abstract: BackgroundArterial and venous thrombosis may share common pathophysiology involving the activation of platelets and inflammatory mediators. A growing body of evidence suggests prothrombotic effect of renin angiotensin system (RAS) including vascular inflammation and platelet activation. We hypothesized that the use of angiotensin converting enzyme inhibitors (ACEIs) or angiotensin receptor blockers (ARBs) plays a role in protecting against venous thromboembolism (VTE) in patients atherosclerosis.MethodsWe cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Medical treatment involves the use spironolactone (aldosterone antagonist or Amiloride) in addition to angiotensin-converting enzyme inhibitors for better control of blood pressure [ 60 ]. Chae et al recently reported that after controlling for factors related to VTE, the use of renin-angiotensin inhibitors was still associated with a significantly lower risk of developing VTE [ 61 ], which may explain why hypernatremic patients in our study receiving steroids were protected against VTE.…”
Section: Discussionmentioning
confidence: 71%
“…Medical treatment involves the use spironolactone (aldosterone antagonist or Amiloride) in addition to angiotensin-converting enzyme inhibitors for better control of blood pressure [ 60 ]. Chae et al recently reported that after controlling for factors related to VTE, the use of renin-angiotensin inhibitors was still associated with a significantly lower risk of developing VTE [ 61 ], which may explain why hypernatremic patients in our study receiving steroids were protected against VTE.…”
Section: Discussionmentioning
confidence: 71%
“…Activation of the renin–angiotensin system promotes a prothrombotic state, with effects on the development of atherosclerotic thrombosis. [ 15 , 41 ] It also increases erythropoiesis,[ 13 , 42 ] leading to raised RDW. Increased activation of the renin–angiotensin system could be another possible explanation for the association between RDW and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The process also elevates plasma erythropoietin level, causing the rise of RDW level. This probably explains why the RDW levels were higher in patients undergoing stroke [ 115 , 116 ].…”
Section: Mechanismsmentioning
confidence: 99%